Developing High Order Thinking Skills-Based Intensive Reading Assessment for the Eleventh Graders of SMA Negeri 1 Pekalongan - Saradifa, Amma Safina; Suwandi, Suwandi (The Journal of Educational Development, 2020)
High Order Thinking Skills (HOTS) has become a hot issue because some experts believe it can improve the students’ problem-solving, creativity, and critical thinking. HOTS-based learning has also been established as part of the 2013 curriculum in Indonesia. However, in reality, many teachers have difficulty applying HOTS in the teaching and learning process. They still use conventional rote learning because of the influence of zoning systems. It make the teachers have not found HOTS-based learning and assessment methods appropriate for heterogeneous students. One of HOTS activities that can be applied in the teaching and learning process is reading. It can encourage the students to establish their ways of thinking, improve their knowledge, and use their ability to solve a problem. Therefore, this study was focused on the issues related to HOTS-based assessment development, especially in terms of intensive reading assessment. Research and Development (R&D) was used as a research design in this study. The samples of this study were the students of XI IPA 2 of SMA Negeri 1 Pekalongan in the academic year of 2019/2020. A questionnaire, interview, observation checklist, and tests were used to collect the data. Also, there are two data analysis techniques, qualitative and quantitative, to ensure that the prototype is categorized as a well-being assessment. The result of this study was shown that the assessment is valid, reliable, and practical. In conclusion, HOTS based intensive reading assessment is applicable to stimulate and measure the critical thinking and creativity of the students’ reading skill.